Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Genetic diversity of provitamin-A cassava (Manihot esculenta Crantz) in Sierra Leone - I. Kamanda; E. T. Blay; I. K. Asante; A. Danquah; B. E. Ifie; E. Parkes; P. Kulakow; I. Rabbi; A. Conteh; J. S. Kamara; H. K. Mensah; J. B. A. Whyte; et al. (Genetic Resources and Crop Evolution, 2020)
Understanding the genetic diversity among accessions and germplasm is an important requirement for crop development as it allows for the selection of diverse parental combinations for enhancing genetic gain in varietal selection, advancement and release. The study aimed to characterize 183 provitamin A cassava ( Manihot esculenta Crantz) accessions and five Sierra Leonean varieties using morphological traits, total carotenoid content and SNP markers to develop a collection for conservation and further use in the cassava breeding program. Both morphological parameters and 5634 SNP markers were used to assess the diversity among the provitamin-A cassava accessions and varieties. Significant differences were observed among the accessions for most of the traits measured. The first five PCs together accounted for 70.44% of the total phenotypic variation based on yield and yield components among the 183 provitamin-A cassava accessions and five Sierra Leonean varieties. The present study showed that provitamin-A cassava accessions in Sierra Leone have moderate to high diversity based on morphological and molecular assessment studies. The similarity index among the 187 and 185 cassava accessions grouped them into 6 and 9 distinct clusters based on morphological and molecular analyses, respectively. A significant positive, but low correlation ( r = 0.104; p < 0.034), was observed between the two dendrograms. The results obtained will serve as a guide and basis of germplasm management and improvement for total carotenoid content, yield and African cassava mosaic disease resistance in Sierra Leone.

Genetic characterization of cassava (Manihot esculenta Crantz) genotypes using agro-morphological and single nucleotide polymorphism markers - Kumba Y. Karim; Beatrice Ifie; Daniel Dzidzienyo; Eric Y. Danquah; Essie T. Blay; Jim B. A. Whyte; Peter Kulakow; Ismail Rabbi; Elizabeth Parkes; Lucky Omoigui; Prince E. Norman; Peter Iluebbey (Physiology and Molecular Biology of Plants, 2020)
Dearth of information on extent of genetic variability in cassava limits the genetic improvement of cassava genotypes in Sierra Leone. The aim of this study was to assess the genetic diversity and relationships within 102 cassava genotypes using agro-morphological and single nucleotide polymorphism markers. Morphological classification based on qualitative traits categorized the germplasm into five different groups, whereas the quantitative trait set had four groups. The SNP markers classified the germplasm into three main cluster groups. A total of seven principal components (PCs) in the qualitative and four PCs in the quantitative trait sets accounted for 79.03% and 72.30% of the total genetic variation, respectively. Significant and positive correlations were observed between average yield per plant and harvest index (r = 0.76 *** ), number of storage roots per plant and harvest index (r = 0.33*), height at first branching and harvest index (0.26*), number of storage roots per plant and average yield per plant (r = 0.58*), height at first branching and average yield per plant (r = 0.24*), length of leaf lobe and petiole length (r = 0.38*), number of leaf lobe and petiole length (r = 0.31*), width of leaf lobe and length of leaf lobe (r = 0.36*), number of leaf lobe and length of leaf lobe (r = 0.43*), starch content and dry matter content (r = 0.99***), number of leaf lobe and root dry matter (r = 0.30*), number of leaf lobe and starch content (r = 0.28*), and height at first branching and plant height (r = 0.45**). Findings are useful for conservation, management, short term recommendation for release and genetic improvement of the crop.

Towards Alternative Approaches for Coupling of a Soft Robotic Sleeve to the Heart - Markus A. Horvath; Claudia E. Varela; Eimear B. Dolan; William Whyte; David S. Monahan; Christopher J. Payne; Isaac A. Wamala; Nikolay V. Vasilyev; Frank A. Pigula; David J. Mooney; Conor J. Walsh; Garry P. Duffy; et al. (Annals of Biomedical Engineering, 2018)

Current knowledge and breeding perspectives for the spider plant (Cleome gynandra L.): a potential for enhanced breeding of the plant in Africa - A. O. Kwarteng; J. Abogoom; R. Adu Amoah; D. Nyadanu; T. Ghunney; K. C. Nyam; J. Z. Ziyaaba; E. O. Danso; D. D. Asiedu; T. Whyte (Genetic Resources and Crop Evolution, 2018)

Current knowledge and breeding avenues to improve upon Frafra potato (Solenostemon rotundifolius (Poir.) J. K. Morton) - A. O. Kwarteng; T. Ghunney; R. Adu Amoah; D. Nyadanu; J. Abogoom; K. C. Nyam; J. Z. Ziyaaba; E. O. Danso; T. Whyte; D. D. Asiedu (Genetic Resources and Crop Evolution, 2018)

Weaving Indigenous science, protocols and sustainability science - Kyle Powys Whyte; Joseph P. Brewer; Jay T. Johnson (Sustainability Science, 2016)

Novel sulfur‐oxidizing streamers thriving in perennial cold saline springs of the Canadian high Arctic - Thomas D. Niederberger; Nancy N. Perreault; John R. Lawrence; Jay L. Nadeau; Randall E. Mielke; Charles W. Greer; Dale T. Andersen; Lyle G. Whyte (Environmental Microbiology, 2009)
Summary The perennial springs at Gypsum Hill (GH) and Colour Peak (CP), situated at nearly 80°N on Axel Heiberg Island in the Canadian high Arctic, are one of the few known examples of cold springs in thick permafrost on Earth. The springs emanate from deep saline aquifers and discharge cold anoxic brines rich in both sulfide and sulfate. Grey‐coloured microbial streamers form during the winter months in snow‐covered regions of the GH spring run‐off channels (−1.3°C to 6.9°C, ∼7.5% NaCl, 0–20 p.p.m. dissolved sulfide, 1 p.p.m. dissolved oxygen) but disappear during the Arctic summer. Culture‐ and molecular‐based analyses of the 16S rRNA gene (FISH, DGGE and clone libraries) indicated that the streamers were uniquely dominated by chemolithoautotrophic sulfur‐oxidizing Thiomicrospira species . The streamers oxidized both sulfide and thiosulfate and fixed CO 2 under in situ conditions and a Thiomicrospira strain isolated from the streamers also actively oxidized sulfide and thiosulfate and fixed CO 2 under cold, saline conditions. Overall, the snow‐covered spring channels appear to represent a unique polar saline microhabitat that protects and allows Thiomicrospira streamers to form and flourish via chemolithoautrophic, phototrophic‐independent metabolism in a high Arctic winter environment characterized by air temperatures commonly below −40°C and with an annual average air temperature of −15°C. These results broaden our knowledge of the physical and chemical boundaries that define life on Earth and have astrobiological implications for the possibility of life existing under similar Martian conditions.

Quantitative linkage genome scan for atopy in a large collection of Caucasian families - Bradley T. Webb; Edwin van den Oord; Anthony Akkari; Steve Wilton; Tina Ly; Rachael Duff; Kathleen C. Barnes; Karin Carlsen; Jorrit Gerritsen; Warren Lenney; Michael Silverman; Peter Sly; et al. (Human Genetics, 2007)

Characterization of lymphocytic infiltrates in progressive multifocal leukoencephalopathy: Co-localization of CD8 + T cells with JCV-infected glial cells - Christian Wüthrich; Santosh Kesari; Woong-Ki Kim; Kenneth Williams; Rebecca Gelman; Derek Elmeric; Umberto De Girolami; Jeffrey T Joseph; Tessa Hedley-Whyte; Igor J Koralnik (Journal of NeuroVirology, 2006)

First record of Mycosphaerella heimii in Australia - G. Whyte; T. I. Burgess; P. A. Barber; G. E. St J. Hardy (Australasian Plant Pathology, 2005)